2019
DOI: 10.1155/2019/8983704
|View full text |Cite
|
Sign up to set email alerts
|

HIF-1-miR-219-SMC4 Regulatory Pathway Promoting Proliferation and Migration of HCC under Hypoxic Condition

Abstract: This paper aims to investigate the function of structural maintenance of chromosome 4 (SMC4) in the progression of hepatocellular carcinoma (HCC) under hypoxic condition. In this study, we found that suppression of SMC4 could inhibit proliferation and migration of HCC cells through inducing G1 phase arrest and affecting process of epithelial-mesenchymal transition (EMT) under hypoxic condition. Moreover, we demonstrated that SMC4 was transcriptionally regulated by hypoxia-inducible factor-1 (HIF-1) under hypox… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
19
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 25 publications
4
19
0
Order By: Relevance
“…HIF-1 in fact, has as an important role under hypoxic conditions in regulating cell proliferation and metabolism. Taken together, our findings stress the leading role of HIF-1α in NE, which is involved in both the melatonin and polo-like kinase cascades 27 30 and interacts directly with both RGS1 and SMC4, which are downstream targets of HIF-1α 30 , 31 . These results are also consistent with our previous data, comparing healthy infants and NE, which showed an upregulation of HIF1A and MALAT1 in NE 9 .…”
Section: Discussionsupporting
confidence: 62%
See 1 more Smart Citation
“…HIF-1 in fact, has as an important role under hypoxic conditions in regulating cell proliferation and metabolism. Taken together, our findings stress the leading role of HIF-1α in NE, which is involved in both the melatonin and polo-like kinase cascades 27 30 and interacts directly with both RGS1 and SMC4, which are downstream targets of HIF-1α 30 , 31 . These results are also consistent with our previous data, comparing healthy infants and NE, which showed an upregulation of HIF1A and MALAT1 in NE 9 .…”
Section: Discussionsupporting
confidence: 62%
“…SMC4 is responsible for regulating chromosome organization and dynamics 32 . Recent studies demonstrated also that SMC4 is associated with tumor progression and invasion and the expression of SMC4 is positively correlated with HIF-1a 30 . RGS1 protein is the most abundant RGS protein in the microglia and is a key gene of the immunomodulatory response to neuroinflammation as well as a key target of different immunological and neurodegenerative diseases such as multiple sclerosis, inflammatory bowel and Parkinson's disease 33,34 .…”
Section: Discussionmentioning
confidence: 95%
“…The ordinate is the actual probability (actual incident rate) of the patient. The red line is the fit line, which represents the actual value corresponding to the predicted value [9]. The decision curve is a useful tool to evaluate the clinical application of the model, which displays estimates of the standardized net benefit by the probability threshold used to categorize observations as 'high risk. '…”
Section: Discussionmentioning
confidence: 99%
“…Studies about microRNA found that miR-219 would be downregulated under hypoxic conditions and upregulated by the suppression of HIF-1α. Moreover, miR-219 can affect the proliferation and migration of hepatocellular carcinoma (HCC) cells under hypoxia [47]. Some botanical active substances inhibit hypoxiainduced tumor cell growth by suppressing EMT.…”
Section: Anti-emt Activity Of Botanical Active Substancesmentioning
confidence: 99%